Clinical and paraclinical characteristics and treatment outcomes of endoscopic retrograde cholangiopancreatography (ercp)-guided biliary stent placement in patients with malignant biliary obstruction - Thao, Tran Van; Oanh, Tran Tu (Tạp chí Khoa học tiêu hóa Việt Nam, 2025)
Objective: To describe the clinical and paraclinical characteristics and evaluate the treatment outcomes of ERCP-guided biliary stenting in patients with malignant biliary obstruction due to cancer. Subject and method: A prospective, non-randomized, longitudinal, convenience-sample interventional study was conducted on 97 patients with malignant biliary obstruction due to cancer who underwent ERCP-guided biliary stenting from December 2019 to January 2024. Result: The study included 97 patients with malignant biliary obstruction due to cancer, with a mean age of 63.1 ± 11.8 years, and 68.0% were male. All patients presented with jaundice, accompanied by anorexia (94.8%), weight loss (88.7%), and abdominal pain (83.5%). Pre-procedure, 100% had elevated total bilirubin, with 58.8% >256.5μmol/L; elevated liver enzymes (AST, ALT, GGT); and hypoalbuminemia in 59.8%. The technical success rate of the initial stent placement was 95.9%, with a higher usage of metal stents (56.7%). After one month, significant improvements were observed in bilirubin, liver enzymes, and creatinine levels (p